2015
DOI: 10.1073/pnas.1503456112
|View full text |Cite
|
Sign up to set email alerts
|

Constraints, independence, and evolution of thermal plasticity: Probing genetic architecture of long- and short-term thermal acclimation

Abstract: Seasonal and daily thermal variation can limit species distributions because of physiological tolerances. Low temperatures are particularly challenging for ectotherms, which use both basal thermotolerance and acclimation, an adaptive plastic response, to mitigate thermal stress. Both basal thermotolerance and acclimation are thought to be important for local adaptation and persistence in the face of climate change. However, the evolutionary independence of basal and plastic tolerances remains unclear. Acclimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
196
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(219 citation statements)
references
References 79 publications
19
196
0
Order By: Relevance
“…2d,e). All metrics thus confirmed that cold acclimation deeply promoted cold tolerance, as previously reported 24 . We then tested whether this clear phenotypic change was associated with detectable changes in phosphorylation network.
Figure 2( a ) Comparison of chill coma recovery dynamics in CA (blue squares) vs. CO (red circles) flies.
…”
Section: Resultssupporting
confidence: 89%
“…2d,e). All metrics thus confirmed that cold acclimation deeply promoted cold tolerance, as previously reported 24 . We then tested whether this clear phenotypic change was associated with detectable changes in phosphorylation network.
Figure 2( a ) Comparison of chill coma recovery dynamics in CA (blue squares) vs. CO (red circles) flies.
…”
Section: Resultssupporting
confidence: 89%
“…Our findings can alternatively be explained by the different fitness consequences of mild stress under chronic (acclimation) and acute (rapid hardening) thermal exposure. Acute exposure to mild stress can actually offer an opportunity for organisms to improve fitness through rapid transient physiological responses [51,77]. Under prolonged exposure, however, the activation of such physiological responses may become costly [73].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have gone further by identifying quantitative trait loci (QTL) for body size and cold tolerance traits involved in adaptation to seasonally varying environments (Tyukmaeva et al 2015; Hangartner et al 2015). Gerken et al (2015) found substantial heritable variation in both short-term and long-term acclimation. They then performed genome-wide association (GWA) mappings on these traits and found the QTL for short-term and long-term adaptations did not overlap, but each resulted in a set of gene candidates sharing similar functions in apoptosis, autophagy, cytoskeletal and membrane structural components, or ion binding and transport.…”
mentioning
confidence: 92%